Clinical Outcomes of Oral Antibiotic Switch in Children with Staphylococcus aureus Bacteremia - Salih Demirhan; Brenda I. Anosike (AVES Yayincilik, 2024)
Objective: Staphylococcus aureus is one of the leading causes of bacteremia in children. In this study, we aimed to evaluate our center's experience on the etiology, management, and outcomes of pediatric Staphylococcus aureus bacteremia (SAB) with particular focus on transitioning to oral antibiotic therapy. Materials and Methods: This retrospective cohort study included children aged ≤ 19 years diagnosed with SAB over a 5-year period. The main outcome was poor clinical outcome related to SAB defined as (1) recurrence of SAB within 30 days after discontinuation of SAB treatment and (2) any-cause mortality within 30 days after detection of SAB. Results: Over a 5-year period, 88 SAB episodes of 76 unique patients were included. The most common source of SAB attributed to central line (n = 34), followed by osteoarticular (n = 24), infections. All patients received at least one day of intravenous (IV) antibiotics and treatment was switched to an oral agent in 45.5% of SAB episodes. Sources of SAB in the oral switch group were osteoarticular (n = 21), skin and soft tissue (n = 7), central line (n = 3), thrombophlebitis (n = 2), head and neck infection (n = 1), and unknown (n = 6). 30-day mortality and SAB recurrence within 30 days after initial treatment completion occurred in 3 and 5 SAB episodes, respectively. None of the patients in oral switch group had poor clinical outcomes. Conclusion: Our study results indicate that 30-day any-cause mortality and SAB-related mortality is low in children. Similar to growing adult literature, oral switch in SAB treatment was not associated with poor SAB outcomes in selected patients.